Formation of actin mesh structures and alpha-smooth muscle actin dynamics in fibroblasts contribute to dermal regeneration in mouse fetus - Kento Takaya; Qi Wang; Yuka Imbe; Hiroyuki Nobusue; Keisuke Okabe; Shigeki Sakai; Noriko Aramaki-Hattori; Kenjiro Hanaoka; Hideyuki Saya; Kazuo Kishi (PLoS ONE, 2025)
In adult mammals and other highly developed animals, incomplete wound healing, scar formation, and fibrosis occur. No treatment for complete tissue regeneration is currently available. However, in mice, at up to 13 days of gestation, early embryonic wounds regenerate without visible scarring. In mouse fetuses, actin cable formation at the epidermal wound margin contributes to regeneration after wounding; however, the relationship between actin behavior and dermal regeneration or scar formation by myofibroblasts is unknown. In the present study, we observed actin dynamics in the wound dermis of mouse fetuses and investigated fibroblast and alpha-smooth muscle actin (α-SMA) properties involved in the switch between regeneration and scar formation in the dermis. In the wound healing process of mouse fetuses, actomyosin bundles develop and contract in a mesh-like pattern in different parts depending on the developmental stage, i.e., in the dermis of E13 (regeneration) and in the fascia of E15 and later (scar formation). Furthermore, in E13 dermal fibroblasts, α-SMA is present in the cytoplasm independently of actin, but in E15 and later myofibroblasts, TGFβ-1 stimulation causes the distribution of α-SMA and actin to coincide, and in E17, when dermal scarring occurs, α-SMA is expressed particularly in the nucleus. The results indicate that reticular contraction by actomyosin is involved in dermal regeneration, and that the discrepancy in the localization of actin and α-SMA in fibroblasts is necessary. The findings may contribute to effective wound regeneration therapy.